PENGARUH PRICE FAIRNESS TERHADAP REPURCHASE INTENTION HIGH END MAKE UP DAN SKIN CARE PADA GENERASI MILENIAL DI JAKARTA - Oktafalia Marisa; Janny Rowena (STIE Wiyatamandala, 2020)
Millennial generation economy behavior is very different from previous generations. Both generation X or even further generations. Generations before millennial save money for the future. While the millennial generation save money for certain purposes. Savings are more short term. So it's easier to spend money on savings and tend not to be ready for future savings. Millennials often spend money beyond their capabilities, the more limited the goods, the more 'stylish' they feel if they can upload it to social media.This study wants to find out whether the purchase decision will then be followed by a repurchase decision on products that are classified as not cheap to satisfy the lifestyle of the generation. The analytical method that researchers use is multiple regression. The purpose of this study is to see whether there is an influence of price fairness on the repurchase intention of high end make up and skin care millennial generation?The results revealed that price fairness had a significant effect on repurchase intention.